Regulation of topographic projection in the brain: Elf-1 in the hippocamposeptal system. - Gao, P P (1996)
The hippocampus and septum play central roles in one of the most important spheres of brain function: learning and memory. Although their topographic connections have been known for two decades and topography may be critical for cognitive functions, the basis for hippocamposeptal topographic projection is unknown. We now report for the first time that Elf-1, a membrane-bound eph family ligand, is a candidate molecular tag for the genesis of the hippocamposeptal topographic projection. Elf-1 is expressed in an increasing gradient from dorsal to ventral septum. Furthermore, Elf-1 selectively allows growth of neurites from topographically appropriate lateral hippocampal neurons, while inhibiting neurite outgrowth by medial hippocampal neurons. Complementary to the expression of Elf-1, an eph family receptor, Bsk, is expressed in the hippocampus in a lateral to medial gradient, consistent with a function as a receptor for Elf-1. Further, Elf-1 specifically bound Bsk, eliciting tyrosine kinase activity. We conclude that the Elf-1/Bsk ligand-receptor pair exhibits traits of a chemoaffinity system for the organization of hippocamposeptal topographic projections.